Boronate based fluorescence (ESIPT) probe for peroxynitrite. Issue 83 (30th September 2016) - Sedgwick, Adam C.; Sun, Xiaolong; Kim, Gyoungmi; Yoon, Juyoung; Bull, Steven D.; James, Tony D.
Abstract : A simple probe for the detection of peroxynitrite was developed incorporating a benzyl boronic ester unit. Abstract : A simple probe for the detection of peroxynitrite was developed incorporating a benzyl boronic ester "protecting" unit. The "protecting" unit of the probe is removed by peroxynitrite to "turn-on" ESIPT fluorescence (4.5 fold enhancement). Furthermore, the probe was cell permeable and was used in cell imaging experiments showing an off–on response towards peroxynitrite, in HeLa and RAW 264.7 cells.